A comparative dynamical analysis of Hebrew texts - Abraham Boyarsky; Pawel Góra (Discrete Dynamics in Nature and Society)
Three Hebrew texts, one of them the Hebrew bible, are investigated using dynamical analysis. First, the average mutual information for each of the texts is determined. The first minimum occurs at T=3 in all three cases, suggesting that 3-letter words are sufficient to study the dynamical properties of the texts. Using 3-letter words as the state space for each of the text, we construct a Markov chain model and compute the relative measure–theoretic entropy for each of the texts and use this tool as a means of comparing the information content of the three texts.